Temporary, Emergent Interorganizational Collaboration in Unexpected Circumstances: A Study of theColumbiaSpace Shuttle Response Effort - Beck, Tammy E.; Plowman, Donde Ashmos (Organization Science, 2014)
In an inductive case study of the Columbia space shuttle disaster response effort, we use observations, archival records, and in-depth interviews with representatives from several responding agencies to explore factors that facilitated this interorganizational collaboration. The Columbia response effort defies conventional theories of collaboration. Relative strangers from dissimilar agencies, without a designated leader or existing structure, quickly collaborated across organizational boundaries on an unprecedented and complex undertaking. We explain how four organizing actions enabled self-organizing and the two-staged development of trust and identity, ultimately leading to a successful unplanned collaboration. We rely on tenets of complexity theory to orient our case study and to propose a grounded theory of temporary, emergent interorganizational collaboration.